Hepatitis E virus RNA in Australian blood donations. Issue 12 (25th September 2016) - Shrestha, Ashish C.; Flower, Robert L.P.; Seed, Clive R.; Keller, Anthony J.; Harley, Robert; Chan, Hiu‐Tat; Hoad, Veronica; Warrilow, David; Northill, Judith; Holmberg, Jerry A.; Faddy, Helen M.
Abstract : BACKGROUND: Hepatitis E virus (HEV) poses a risk to transfusion safety. In Australia, locally acquired HEV is rare and cases are mainly reported in travelers returning from countries endemic for HEV. The risk posed by HEV to transfusion safety in Australia is unknown; therefore, we aimed to measure the rate of current HEV infection in Australian blood donations. STUDY DESIGN AND METHODS: A total of 14, 799 blood donations were tested for HEV RNA by transcription‐mediated amplification, with confirmatory testing by reverse transcription–polymerase chain reaction. Viral load quantification and phylogenetic analysis was performed on HEV RNA–positive samples. RESULTS: One (0.0068%; 95% confidence interval [CI], 0.0002%‐0.0376%) sample was confirmed positive for HEV RNA, resulting in a risk of collecting a HEV‐viremic donation of 1 in 14, 799 (95% CI, 1 in 584, 530 to 1 in 2, 657). The viral load in this sample was approximately 15, 000 IU/mL, and it was determined to be Genotype 3. DISCUSSION: Our finding of 1 in 14, 799 Australian donations positive for HEV RNA is lower than that from many other developed countries; this is consistent with the relatively low seroprevalence in Australia. As this HEV RNA–positive sample was Genotype 3, it seems likely that this infection was acquired through zoonotic transmission, either within Australia or overseas in a developed nation. HEV has the potential to pose a risk to transfusion safety in Australia; however, additional, larger studies are required to quantify the magnitude of this risk.